Sociodemographic and psychological determinants of physical activity level among form four students in Selangor, Malaysia - Leong, In Tyng (2018)
Adolescents reduce their physical activity level as they aged. Socio-demographic and psychological factors are the important factors that closely related to physical activity level. The objective of this study was to determine the socio-demographic and psychological factors that associated with physical activity among Form Four students in Selangor. A total of 1158 Form Four students (aged 16.1 ± 0.2 years old) were selected via clustered random sampling method. All consented Form Four students from randomly selected schools in Selangor participated in this cross-sectional study. A validated and reliable self-administered questionnaire was used for data collection on socio-demographic factors, sedentary activities, psychological factors and anthropometry measurement. The outcome of this study was level of physical activity which was collected using International Physical Activity Questionnaire (IPAQ). The physical activity level of the participants was 47.4%, 39.4% and 13.2% respectively for high, moderate and low physical activity. Socio-demographic factors that had significant association between physical activity level were gender (χ2 = 48.442, p < 0.001), ethnicity (χ2 = 6.932, p = 0.031), number of siblings (χ2 = 6.335, p = 0.042), household size (χ2 = 6.432, p = 0.040), father’s education level (χ2 = 15.002, p = 0.001) and mother’s education level (χ2 = 7.259, p = 0.027). Sedentary activities were not significantly associated with physical activity except reading (χ2 = 9.041, p = 0.011) and revision (χ2 = 11.058, p = 0.004). Psychological factors that had significant association with physical activity level were introjected regulation (F (2, 1155) = 10.720, p < 0.001), identified regulation (F (2, 1155) = 22.976, p < 0.001), intrinsic regulation of motivation (χ2 = 52.805, p < 0.001), social physique anxiety (F (2, 1155) = 3.934, p = 0.020), stress (F (2, 1155) = 14.628, p < 0.001), self-esteem (χ2 = 17.927, p < 0.001) and physical activity level self-efficacy (F (2, 1155) = 43.570, p < 0.001). No significant association was found between anthropometry measurement and physical activity level. Multinomial logistic regression analysis on the predicting factors for active physical activity among the students showed that intrinsic regulation of motivation, number of siblings, father’s education level, time spent on tuition, revision and reading and physical activity self-efficacy were significant in explaining high physical activity whereas only physical activity self-efficacy was found to be significant in explaining moderate physical activity. This study suggests that intrinsic regulation and physical activity self-efficacy should be taken into consideration when promoting physical activity intervention among adolescents.